'The Asymptotic Number of Connected d-Uniform Hypergraphs' — CORRIGENDUM. (14th October 2014) - BEHRISCH, MICHAEL; COJA-OGHLAN, AMIN; KANG, MIHYUN
Abstract : The authors would like to rectify a mistake made in Theorem 1.1 of their article (Behrisch, Cojaa-Oghlan & Kang 2014), published in issue 23 (3). The text below explains the changes required.